Strategic Management Approaches for Enhancing English-Speaking Proficiency in Language Education - Rifa Rizkia Fakhrini; Na'imah; Irmawati; Irvan Zidny (Universitas Subang, 2024)
This study explores effective strategies for teaching English speaking skills and the factors that influence implementing these strategies. The study discussed the strategies used in speaking learning, why they are chosen, and their implications for students speaking success. The strategies referred to in this study encompass methods, resources, and media used in achieving success in learning to speak English. The research method employed is qualitative with a case study approach. The study was conducted in March 2023 at some schools and English courses, with ten teachers serving as informants. Data collection was carried out through indirect interviews via WhatsApp and GoogleForm. The main findings show that role-play and chain drill methods are the most frequently applied strategies and are considered effective in improving students speaking skills. The main factors that influence the use of these strategies include students interest and the relevance of the material. The implications of this study highlight the importance of selecting strategies that are appropriate to students characteristics and learning contexts, and this study shows the need to adapt teaching methods based on the availability of resources and environmental support. The results of this study provide insights for educators to design and implement more effective speaking learning strategies and encourage further discussion on innovation in English language learning.